JUEGOS DIDACTICOS PARA PROMOVER EL DESARROLLO DE LA MOTRICIDAD FINA EN LOS ESTUDIANTES DE EDUCACIÓN INICIAL II - PLUA JATIVA NAYDELIN MILENA (2024)
The present research is titled Didactic games to promote the development of fine motor skills in students of Initial Education II, fine motor skills are a set of broad movements in the first years of life and their subsequent exploration through the body, giving rise to movements more precise. in the future, considering that educational games are a means of creation and communication, to obtain benefits from them it is essential to understand when and why to apply them, since each of them has a purpose, therefore the objective of the research is Determine the impact of educational games to promote the development of fine motor skills in Initial Education II students. To comply with this, a cross-sectional non-experimental methodological design was used, whose scope is descriptive with a mixed approach. The research method is inductive where field research will be used in addition to techniques such as observation, survey and interview; whose instruments were questionnaires and observation sheets whose structures were made up of questions validated and approved by the tutor teacher herself, which were applied, resulting in around 85% of the students showing improvement in their fine motor skills after seeing the participants in different didactic games concluding that these have a fundamental role in fine motor skills, considering that their proper application contributes to the development of the infant, preparing them for better development in daily life.